2011
DOI: 10.1111/j.1745-6584.2010.00791.x
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Thermal Response Test Analysis Using Pumping Test Concepts

Abstract: The design of ground-coupled heat pump systems requires knowledge of the thermal properties of the subsurface and boreholes. These properties can be measured with in situ thermal response tests (TRT), where a heat transfer fluid flowing in a ground heat exchanger is heated with an electric element and the resulting temperature perturbation is monitored. These tests are analogous to standard pumping tests conducted in hydrogeology, because a system that is initially assumed at equilibrium is perturbed and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(54 citation statements)
references
References 34 publications
2
48
0
4
Order By: Relevance
“…Figure 9 compares the observed behavior during the test and the expected behavior according to Equation (13). Up to 30 °C, the increase in conductivity is coherent with the proposed law.…”
Section: Petrophysical Considerations Regarding Electrical Conductivitysupporting
confidence: 55%
See 1 more Smart Citation
“…Figure 9 compares the observed behavior during the test and the expected behavior according to Equation (13). Up to 30 °C, the increase in conductivity is coherent with the proposed law.…”
Section: Petrophysical Considerations Regarding Electrical Conductivitysupporting
confidence: 55%
“…However, such models require the knowledge of the parameters governing groundwater flow (e.g., hydraulic conductivity and specific storage) and heat transport (e.g., thermal conductivity, volumetric heat capacity, flow rate). In situ tests, such as thermal response tests [12,13] or laboratory measurements [14] are sometimes possible, but the values obtained may deliver only well-centered information or may not always (if not at all) be representative of in situ conditions at a larger scale. Such data are often scarce if not missing and authors often have to rely on standard calculation charts, values found in the literature, or simply default values implemented in standard software (e.g., [15][16][17][18]).…”
Section: Introductionmentioning
confidence: 99%
“…For the line source, the absence of the qR b term in Equation 11 means that the model is forced through the origin, when potentially there may still be some power applied due to the operation of the circulation pump, and/or due to other external influences. Recovery data are traditionally viewed as more reliable than heat injection data due to the absence of power supply variations and the fact that g can be determined independently of R b [49]. However, it comes with the disadvantage of increased test costs.…”
Section: Analysis Methods and Approachmentioning
confidence: 99%
“…In addition to examining the performance of complex shape GHEs, TPTs can also be used to examine the actual performance of an installed conventional BHE. Obtaining the heat exchange rate is important because many uncertainties affect the construction and design of BHEs, such as the geometry of the U-tubes (torsion and bending of pipe legs), uneven packing of the grouting or backfill, unverified subsurface heat-transfer phenomena, and uncertain ground properties, as noted in Bernier (2002) ;Raymond, et al (2011);Spitler and Gehlin (2015); Witte (2013).…”
Section: Introductionmentioning
confidence: 99%